WARD COMMITTEES AND DECISION-MAKING IN LOCAL GOVERNMENT - MKHIZE, TEBOHO GODFREY DANIEL (My University, 2011)
The ward participatory system in the South African local sphere of government as stipulated in the Local Government: Municipal Systems Act, (No 32 of 2000) can be viewed as a legislative initiative to introduce a paradigm shift in the civil society‟s both the practice and conceptualisation of participatory democracy. Essentially, this piece of legislation is a key proponent for a shift away from a passive to active citizenship in the governance discourse in the case. Hence, this study seeks to explore the role and means by which ward committees influence municipal decisions in order to capture an indication whether their involvement in this regard amounts to some degree of active or passive participation. And to further take stock of the gains that have been made since their involvement in the decision-making of local municipalities. Firstly, the study tests the perceptions of ward and non-ward committee members, from three ward committees from the Ekurhuleni Municipality Council on the impact made by ward committees on municipal decision- making through observation, documentation and interviews. Second, the study analyses the responses using existing literature on participatory democracy. One finding of the study is a generally strong sense of satisfaction about the use of the ward participatory system in municipal decision-making. Another is a generally satisfactory level of proof about the impact of ward committees in their wards. The study, however, shows an inconsistent administrative support being given to ward committees. Finally, the study makes recommendations on how to improve on the quality of contribution of ward committees in municipal decision-making
MM - P&DM
Keywords: Ward committees; Local government; Local authorities; Municipalities